2013
DOI: 10.1007/s10461-012-0398-4
|View full text |Cite
|
Sign up to set email alerts
|

Unprotected Receptive Anal Intercourse Among Men Who have Sex with Men in Brazil

Abstract: The aim of this study was to assess factors associated with unprotected receptive anal intercourse (URAI) in a sample of MSM recruited by respondent driven sampling in Brazil. Among 3,449 participants, 36.5 % reported URAI. Final logistic model indicated that living with a male partner, illicit drug use, having stable partnership, having sex with men only, having few friends encouraging condom use, and high self-perceived risk for HIV infection were characteristics independently associated with URAI. Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 10 publications
2
26
1
5
Order By: Relevance
“…Resultado similar também foi encontrado no trabalho realizado por Deb et al 15 . Contudo, esse fato se torna preocupante quando analisamos os resultados de Rocha et al 4 , que encontraram um elevado risco de prática do sexo anal receptivo desprotegido entre os HSH que vivem com um parceiro masculino ou têm um parceiro estável, dos quais uma grande proporção destes também relatou relações sexuais com um parceiro casual ou comercial ao mesmo tempo.…”
Section: Fatores De Vulnerabilidade Modelos Intermediáriosunclassified
See 1 more Smart Citation
“…Resultado similar também foi encontrado no trabalho realizado por Deb et al 15 . Contudo, esse fato se torna preocupante quando analisamos os resultados de Rocha et al 4 , que encontraram um elevado risco de prática do sexo anal receptivo desprotegido entre os HSH que vivem com um parceiro masculino ou têm um parceiro estável, dos quais uma grande proporção destes também relatou relações sexuais com um parceiro casual ou comercial ao mesmo tempo.…”
Section: Fatores De Vulnerabilidade Modelos Intermediáriosunclassified
“…Estudo nacional realizado entre HSH de dez municípios brasileiros, utilizando a metodologia Respondent Driven Sampling (RDS), mostrou uma preocupante situação epidemiológica. A prevalência global do HIV foi de 14,2% 3 com variações de 5,2 a 23,7% entre as cidades, e a proporção de relações anais receptivas desprotegidas foi de 36,5% 4 . Da mesma forma, o nível de conhecimento em HIV/AIDS entre os HSH foi avaliado e encontrou-se 40,7% da amostra com níveis de conhecimento abaixo da média 5 .…”
Section: Introductionunclassified
“…This group has progressively increased its contribution to AIDS cases among men, rising from 36.2% in 2001 to 48.3% in 2011 (3) . In 10 Brazilian cities, almost half (47%) of MSM lacked risk perception concerning HIV infection, 37.5% have never been tested for HIV, and 36.5% participated in unprotected receptive anal intercourse (20) . These results suggest that in the State of Amazonas, the largest proportion of AIDS cases over time has been among people in their twenties and mid-thirties with no sex disparities.…”
Section: Critical Evaluation Of Changes Observed Within the Context Omentioning
confidence: 99%
“…In general, “stable” or primary partnerships are associated with a greater perception of commitment between the partners involved, while “non-stable” partnerships, including casual, anonymous or transactional sexual relations, typically do not carry comparable levels of emotional intimacy [14]–[17]. Accordingly, UAI has been more commonly reported in primary partnerships when compared to casual partnerships among both HIV-infected and HIV-uninfected MSM [10], [11], [18], suggesting an association between partnership type and willingness to engage in UAI. The greater intimacy presumed in “stable” partnerships can be seen as both protective (supporting open communication about HIV and STI, and encouraging mutually protective behavior within the partnership), and potentially harmful (inhibiting condom use within a partnership which is incorrectly believed to be monogamous and free of infection) [14]–[17].…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has documented an association between partnership type and UAI in diverse populations worldwide [7], [10], [12], [19], [20], few studies have investigated the relationship between partnership type and UAI among MSM and TGW in Latin America [11], [21]. Modeling estimates from the Prevention Umbrella for MSM in the Americas (PUMA) project have suggested that UAI drives the HIV epidemic in Peru, with approximately one-third of new HIV cases believed to occur in primary partnerships [1].…”
Section: Introductionmentioning
confidence: 99%